Stealth cryptococcus in an immunocompetent patient - Emily Ryan; Gia Jackson; Larry Nichols (University of São Paulo, 2024)
Cryptococcosis occurs primarily in immunocompromised patients. It is difficult to suspect in an immunocompetent patient presenting with a headache. The clinical manifestations of cryptococcosis can be subtle in a patient whose immune system is responding, but inadequate. This is the report of a case of fatal cryptococcosis initially misdiagnosed as a sinus headache on the basis of a telephone call, and then misdiagnosed as aseptic meningitis on the basis of mild findings and negative cerebrospinal fluid cultures. Autopsy revealed unsuspected severe cryptococcal meningoencephalitis. Cerebrospinal fluid nuclear acid amplification (NAA) panels including Cryptococcus should enable the diagnosis of unsuspected cryptococcal meningitis in most cases, but can be false positive, which could be adjudicated by cryptococcal antigen and culture. It will remain important to test for cryptococcal antigen and to maintain a broad differential diagnosis for all patients with meningitis.